2021
DOI: 10.1111/ijcp.14074
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists’ awareness of COVID‐19 and perceptions of their roles, barriers, and roles of policymakers: Exploring the Middle East and North Africa (MENA)

Abstract: Background The coronavirus disease (COVID‐19) was declared in January 2020 as a public health emergency of international concern. The Middle East and North Africa (MENA) suffered from several pandemics previously. Pharmacists have vital roles to play to prevent the spread of this virus. Objectives To assess the COVID‐19 awareness amongst pharmacists from Arabic‐speaking countries located in the MENA region, and to assess their perspectives of their role, barriers, and roles of the educational institutions/phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
1
6
0
2
Order By: Relevance
“…Our study findings reported that almost two-thirds of them had good/very good knowledge. Also, the majority closely followed the latest coronavirus updates on treatments and updated their information mostly from the WHO reports, health authorities, and social media, similar to findings reported by other pharmacists in the MENA region [ 23 , 24 ]. It is crucial that pharmacists worldwide stay updated and use a reliable source of information during a pandemic.…”
Section: Discussionsupporting
confidence: 58%
“…Our study findings reported that almost two-thirds of them had good/very good knowledge. Also, the majority closely followed the latest coronavirus updates on treatments and updated their information mostly from the WHO reports, health authorities, and social media, similar to findings reported by other pharmacists in the MENA region [ 23 , 24 ]. It is crucial that pharmacists worldwide stay updated and use a reliable source of information during a pandemic.…”
Section: Discussionsupporting
confidence: 58%
“…Worldwide, during the pandemic, there was a greater dependence on community pharmacists as they were the first point of contact to fulfill the need of the public as they were one of the few places that stayed open during lockdowns. 35 , 36 Globally, pharmacists have been given numerous opportunities and legal extensions of their role to fight COVID-19 and decrease the health burden on the country; 36 , 37 for example, from the current study, 33.6% agreed that pharmacists had a role in providing advice on how to use some devices such as oximeter and the thermometer which were extensively used by individuals during the COVID-19 pandemic, moreover 33.0% agreed that pharmacist had a role in sending medications to homes during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…37 Sources of information were versatile; most information came from the Ministry of Health and the contribution of social media was lower than that in the Middle East and North Africa (MENA) region. 38 In general, pharmacists had a positive attitude towards their role in the COVID-19 pandemic. This proactive role towards the COVID-19 pandemic was expressed by pharmacist in other studies.…”
Section: Discussionmentioning
confidence: 99%